Cat among the pigeons - Christie, Agatha, 1890-1976. (New York : HarperPaperbacks, 1987)
Hercule Poirot investigates when an unsuspecting student becomes the target of a killer who is terrorizing a famous school for girls.
Young Adult
Keywords: Poirot, Hercule (Fictitious character) -- Fiction; Private investigators -- England -- Fiction; Mystery fiction; Poirot, Hercule (Fictional character) -- Fiction; Private investigators -- Fiction; Detective and mystery stories